A Study of Parents’ Satisfaction towards Chinese Subjects in Nantawan International School, Thailand - Liu, Rong Rong; Ye, Yan (Scholar: Human Sciences, 2016)
This research tried: to identify the demographics of learning Chinese subjects’ students, including their nationality, Grade, parental highest education level and family income; to determine the parents’ satisfaction towards current two Chinese subjects, including learning Chinese as a native language subject and learning Chinese as a second language subject in Nantawan International School; and to compare the parents’ satisfaction between learning Chinese as a native language subject and learning Chinese as a second language subject in Nantawan International School. The examined population comprised of all 105 parents from Grade1-Grade 6 of Nantawan International School. The research was a quantitative research by using a designed questionnaire. The returned valid questionnaires reached 100% and were analyzed by Means, Standard Deviations, Independent samples t-test (two-tailed). The research major findings included: the parents’ satisfaction towards both Chinese subjects in Nantawan International School was regarded as “satisfied”; and there were no significant differences between the parents’ satisfaction of learning Chinese as a native language subject and learning Chinese as a second language subject.